Model Pembelajaran Kebugaran Jasmani Melalui Permainan (3L Healthy) Siswa SLB di Tegal - Faizal Anwar Al Mukharom; Ipang Setiawan; Adi S; Agus Pujianto (Indonesian Journal for Physical Education and Sport, 2024)
The background of this research problem is the lack of variation of PE learning models in State SLB in Tegal. The purpose of this study was to create and develop a 3L Healthy game product for physical fitness learning in State SLB in Tegal. This type of research is development research (Research and Development). Data collection techniques using observation, interviews, questionnaires, and documentation. The results of this study show a modified 3L Healthy game product that goes through several stages, namely: 1) adaptive PE education expert validation test gets a percentage score of 82% (good), 2) small-scale test PE learning experts get a percentage score of 94% (very good), 3) the average score of small-scale test students is 79%, 4) large-scale test PE learning experts get a percentage score of 92% (very good), 5) ) the average score of large-scale test students is 88% (good). The development of a physical fitness learning model through modified games (3L Healthy) for State SLB students in Tegal is included in the good category and can be said to be suitable for use.